The sensitivity of algae to the exposure of telmisartan - Aubakirova, B.N.; Beisenova, R.R.; Zhurmanova, N.Sh.; Tulegenova, S.Ye.; Rymbay, N. (Fundamental and Experimental Biology, 2019)
Nowadays, everyday people apply various pharmaceuticals. However, after their consumption drugs excrete to wastewater treatment plant, where they cannot be eliminated totally. As the result they released to surface waters. Many scientists concerned about the effect of medical substances on aquatic biota. The issue of pharmaceutical contamination is not well studied in Kazakhstan in comparison with EU countries. Therefore, it is significant to do ecotoxicological research on pharmaceutical ingredients. The aim of our study was to assess the effect of telmisartan on the growth of Chlorella species. Telmisartan was selected as currently it is one of the priority pharmaceuticals based on risks to aquatic biota in Kazakhstan. We estimated exposure of substance in 5–15 mg/L concentrations. According to the results, high concentration of our medical substance had significant impact to the growth algae, it led to 83.93±0.13 % of growth inhibition. The half maximal inhibitory concentration of telmisartan on algae was 6.16 mg/L. Furthermore, we calculated the growth rate of Chlorella species. We found that growth rate decreased in six times on algae in concentration 15 mg/L in comparison with controls. The following results showed that Chlorella speciesare vulnerable to the exposure. of pharmaceuticals.